Effect of particle surface corrugation on colloidal interactions - Kämäräinen, Tero; Tardy, Blaise L.; Javan Nikkhah, Sousa; Batys, Piotr; Sammalkorpi, Maria; Rojas, Orlando J. (Journal of Colloid and Interface Science, 2020)
Hypothesis: Production of corrugated particles generally introduces several morphological heterogeneities, such as surface roughness and local variations in the corrugation pattern, which are known from model system studies to significantly alter the colloidal interaction energy. Thus, realistic particle morphologies need to be investigated and compared to simple model shapes to yield insights into how interactions are influenced by such morphological heterogeneities. Experiments: We applied the surface element integration method to study the colloidal interactions of electron tomography-based, realistic, corrugated colloidal particles and their symmetric, concave polyhedral analogs by differentiating local surface features to vertices, ridges and ridge networks. We applied molecular modelling to assess the surface access of these features. Findings: Significant mixing of the interaction energy was found between the different surface features. Larger and smaller energy barrier heights and secondary minimum depths were observed compared to the concave polyhedral models with similar volume or surface area depending on the contacting surface feature. Analysis of surface area distributions suggests that the deviations originate from the altered effective contact distance as a result of surface roughness and other morphological heterogeneities. We also found that the surface access of nanoparticles is greatly impaired at the crevices between the surface corrugations.
Created from Fastlane, Scopus look-up
Keywords: Coarse-grained simulation; Colloids; Concave polyhedron; Corrugated particles; DLVO; Electron tomography; Interparticle forces; Lignin; Surface element integration